PENGARUH KETERLIBATAN KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA - Andre Aldi Saputra (UM. Bengkulu, 2022)
The purpose of this study was to determine the effect of work involvement, work motivation on job satisfaction (Case Study of Employees of PT. Bukit Barisan Sandjaya Ulma).This study uses a causal associative research method using a quantitative approach. The population in this study were employees of PT. Bukit Barisan Sandjaya Ulma totaling 80 people with sampling using total sampling and data collection techniques using observation and questionnaires.Based on the research results and hypotheses, it shows that work involvement (X1) is t_hit>t_tabel(4.643 > 1.664) and (sig = 0.000 < 0.050), and work motivation (X2) is t_hit>t_tabel (2.092 > 1.664) and (sig = 0.040 < 0.050), Partially the two variables of work involvement and work motivation have a significant effect on job satisfaction. The results of the f test show that Fcount > Ftable (21,589 > 3,965) and (sig = 0.000 < 0.050), Simultaneously Significantly Affects Job Satisfaction. Keywords: Job Involvement, Work Motivation, Job Satisfaction